Classifying the Evidence Base of Classwide Peer Tutoring for Students with High-Incidence Disabilities. Issue 1 (2nd January 2017) - Cook, Sara Cothren; Cook, Bryan G.; Cook, Lysandra
ABSTRACT: Evidence-based reforms that emphasize the identification and implementation of empirically validated practices are at the forefront of educational research, and recently, the Council for Exceptional Children (CEC; 2014) published a set of standards for establishing evidence-based practices in special education. Although 30 years of research supports the effectiveness of ClassWide Peer Tutoring (CWPT), an instructional strategy intended to increase engagement and improve academic outcomes for students with disabilities, a formal evidence-based review has not yet been conducted on the practice. The purpose of this study is to examine whether CWPT, as developed by the Juniper Gardens Children's Project at the University of Kansas, can be considered an evidence-based practice for academic outcomes of students with high incidence disabilities using the CEC standards. Sixteen single-case design studies met inclusion criteria; no studies addressed all the required quality indicators. Although results of multiple studies show that CWPT had positive effects, the lack of methodologically sound studies supporting the practice means that CWPT is not considered an evidence-based practice according to the CEC (2014) standards. Implications for research and practice are discussed.